ENFORCEMENT OF NOTARY CODE OF ETHICS AGAINST PROMOTION VIOLATIONS THROUGH INTERNET MEDIA IN INDONESIA: PENEGAKAN KODE ETIK NOTARIS TERHADAP PELANGGARAN PROMOSI MELALUI MEDIA INTERNET DI INDONESIA - Ananda, Adhe Ismail (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2024)
This study discusses the enforcement of the notary code of ethics against promotional violations through internet media in Indonesia. As a public official, Notary have a great responsibility in maintaining integrity and professionalism in carrying out their duties. However, in the current digital era, promotion through internet media is a complex issue due to the prohibition in the notary Code of ethics related to self-promotion. This study uses juridical-normative approach and descriptive-analytical approach to analyze the legal regulations and notary practices related to promotion in the internet media. The results showed that violation of this promotion ban may result in disciplinary sanctions from the notary Supervisory Board. However, the effectiveness of enforcing the code of conduct is still a matter of debate, with challenges in consistency and transparency in enforcing the rules. The importance of enforcing this code of ethics is not only as law enforcement, but also as a preventive effort to maintain the integrity of the notary profession and public trust. Thus, this study provides a more comprehensive understanding of the enforcement of the notary code of ethics against promotional violations through internet media in Indonesia.